Corporate Social Responsibility (CSR) Efficiency Approach with the Establishment of a State Institution Managing Funding and CSR Programs - Agustinus Soetrisno (Universitas Pelita Harapan, 2021)
CSR is an activity that provides broader benefits in various social aspects such as education, health, community empowerment or environmental preservation. CSR actions applied as a strategy will only cause irregularities in the use of funds owned by the company which can trigger to damage to the company's financial performance. This is thought to be due to the fact that there are quite a lot of funds budgeted with the CSR implementation which is not supervised, which causes inefficiency. This study aims to determine and analyze the provisions of the laws and regulations that govern CSR related to the obligations of Limited Liability Companies in the Indonesian legal system and to find out and analyze the implementation of company obligations to implement CSR in Indonesia and find solutions to corporate liability arrangements such as Limited Liability Companies (PT), Enterprises. Micro, Small and Medium Enterprises (UMKM) and other businesses carry out CSR to be useful in accordance with that CSR. The approach used is the Legislative Law approach and the case approach. From the research results it is known that 1). CSR regulations concerning the obligation of PT to implement it in the Indonesian legal framework are regulated in several laws but there are 2 (two) laws that specifically regulate CSR but the two laws are inconsistent with regard to sanctions if these obligations are violated, 2) Implementation of PT obligations implementing CSR in Indonesia is a program carried out by the company that is not in accordance with the community needs, is carried out individually, is moving and it’s not sustainable, there is no provision that regulates the amount of funds and there is no supervision from the local government in managing CSR. The occurrence of overlapping laws and regulations so that the implementation of the CSR program does not match the policies issued by the local government. CSR funds are misused and even corrupted by local officials and there is no evaluation by the company because it is more concerned with profit in carrying out CSR. 3). Regulating company obligations such as Limited Liability Companies (PT), Micro, Small and Medium Enterprises (MSMEs) and other businesses implementing CSR so that it is useful, it is necessary to establish a state institution that manages CSR and accommodates the companies’, government’s and society interests so that the CSR program can run efficiently, precisely targeted and continuously.